Human umbilical cord mesenchymal stem cell-derived exosomal miR-27b attenuates subretinal fibrosis via suppressing epithelial–mesenchymal transition by targeting HOXC6 - Dongli Li; Junxiu Zhang; Zijia Liu; Yuanyuan Gong; Zhi Zheng (Stem Cell Research & Therapy, 2021)
Abstract Background and aim Subretinal fibrosis resulting from neovascular age-related macular degeneration (nAMD) is one of the major causes of serious and irreversible vision loss worldwide, and no definite and effective treatment exists currently. Retinal pigmented epithelium (RPE) cells are crucial in maintaining the visual function of normal eyes and its epithelial–mesenchymal transition (EMT) is associated with the pathogenesis of subretinal fibrosis. Stem cell-derived exosomes have been reported to play a crucial role in tissue fibrosis by transferring their molecular contents. This study aimed to explore the effects of human umbilical cord-derived mesenchymal stem cell exosomes (hucMSC-Exo) on subretinal fibrosis in vivo and in vitro and to investigate the anti-fibrotic mechanism of action of hucMSC-Exo. Methods In this study, human umbilical cord-derived mesenchymal stem cells (hucMSCs) were successfully cultured and identified, and exosomes were isolated from the supernatant by ultracentrifugation. A laser-induced choroidal neovascularization (CNV) and subretinal fibrosis model indicated that the intravitreal administration of hucMSC-Exo effectively alleviated subretinal fibrosis in vivo. Furthermore, hucMSC-Exo could efficaciously suppress the migration of retinal pigmented epithelial (RPE) cells and promote the mesenchymal–epithelial transition by delivering miR-27b-3p. The latent binding of miR-27b-3p to homeobox protein Hox-C6 (HOXC6) was analyzed by bioinformatics prediction and luciferase reporter assays. Results This study showed that the intravitreal injection of hucMSC-Exo effectively ameliorated laser-induced CNV and subretinal fibrosis via the suppression of epithelial–mesenchymal transition (EMT) process. In addition, hucMSC-Exo containing miR-27b repressed the EMT process in RPE cells induced by transforming growth factor-beta2 (TGF-β2) via inhibiting HOXC6 expression. Conclusions The present study showed that HucMSC-derived exosomal miR-27b could reverse the process of EMT induced by TGF-β2 via inhibiting HOXC6, indicating that the exosomal miR-27b/HOXC6 axis might play a vital role in ameliorating subretinal fibrosis. The present study proposed a promising therapeutic agent for treating ocular fibrotic diseases and provided insights into the mechanism of action of hucMSC-Exo on subretinal fibrosis.